Biomass of benthic foraminifera in sediments of the Sea of Okhotsk. - Basov, Ivan A; Khusid, Tatyana A (PANGAEA, 1983)
A study of distribution of live individuals of benthic foraminifera in sediments of the Sea of Okhotsk and of the Northwestern Basin of the Pacific Ocean shows that they can be present in sediments up to depth of 30 cm and probably can live there for long periods, sometimes forming high concentrations. Living individuals in the subsurface layer often account for more than 50% of total biomass, which varies from 1 to 21 g/m**2 in different morphological structures. The largest biomass values are attained in underwater rises embedded in relatively warm, oxygen-saturated Pacific waters. Minimum total biomass concentrations occur in deep-water depressions where stagnation phenomena are observed. Foraminifera biomass everywhere decreases gradually with increasing depth from the surface of sediments regardless of relief, depth, and nature of sediments.
Abundance and biomass of benthic foraminifera in bottom sediments from the Sea of Okhotsk and the Pacific Ocean
Keywords: Akademik Kurchatov; AKU26A; Archive of Ocean Data; ARCOD; Counting, foraminifera, benthic; DEPTH, sediment/rock; Foraminifera, benthic; Foraminifera, benthic, number of species; Foraminifera, benthic living; GC; Gravity corer; Pacific Ocean; Sea of Okhotsk; VITYAZ6675; VITYAZ6676; VITYAZ6677; VITYAZ6678; VITYAZ6681; VITYAZ6682; VITYAZ6683; VITYAZ6684; VITYAZ6686; VITYAZ6687; VITYAZ6688; VITYAZ6690; VITYAZ6691; VITYAZ6692; VITYAZ6693; VITYAZ6694; VITYAZ6695; VITYAZ6697